A Decade of Research on Evaluation: A Systematic Review of Research on Evaluation Published Between 2005 and 2014. (September 2017) - Coryn, Chris L. S.; Wilson, Lyssa N.; Westine, Carl D.; Hobson, Kristin A.; Ozeki, Satoshi; Fiekowsky, Erica L.; Greenman, Gregory D.; Schröter, Daniela C.
Although investigations into evaluation theories, methods, and practices have been occurring since the late 1970s, research on evaluation (RoE) has seemingly increased in the past decade. In this review, 257 studies published in 14 evaluation-focused journals over a 10-year period (between 2005 and 2014) were identified as RoE and then classified according to Henry and Mark's and Mark's taxonomies of RoE. The majority of RoE published in evaluation-focused journals consists of descriptive studies and, to a lesser extent, comparative studies of evaluation practices. Few investigations, however, address questions pertaining to values or valuing in evaluation, ethics, or evaluation consequences. Gaps in and an agenda for future RoE are discussed.